Impact of Personalized Learning Paths on Student Motivation and Achievement in Online High School Programs in Pakistan - Khan, Mariam (International Journal of Online and Distance Learning, 2024)
Purpose: The aim of the study was to investigate the impact of personalized learning paths on student motivation and achievement in online high school programs in Pakistan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Tailored learning experiences boost intrinsic motivation by offering autonomy and relevance, while goal-setting and progress tracking contribute to improved academic performance and engagement. These findings highlight the potential of personalized learning to meet diverse student needs and enhance educational outcomes in Pakistani online high school settings. Unique Contribution to Theory, Practice and Policy: Self-determination theory (SDT), social cognitive theory (SCT) & constructivist learning theory may be used to anchor future studies on the impact of personalized learning paths on student motivation and achievement in online high school programs in Pakistan. Implement ongoing professional development programs for educators to effectively implement and support personalized learning strategies. Develop and advocate for educational policies that support the implementation of personalized learning paths in online high school programs. Policies should address funding allocations, technology infrastructure upgrades, and guidelines for equitable access to personalized educational resources.